Penilaian Kepuasan Kerja Karyawan Terhadap Sistem Pengelolaan Sumberdaya Manusia di Rumah Sakit - Ria Chandra Kartika (Puslitbang Sinergis Asa Professional, 2019)
Assessment of employee’s satisfaction assessment is an important thing to do by the hospital management. The data can be used as a source of information about resource management systems in hospitals, reducing turnover, and improving hospital performance. The objectives of this study was to measure job satisfaction level of the employee at RSIA NUN Surabaya This study is crossectional design study. The sample was 45 employees in RSIA NUN Surabaya were selected using proportional random sampling techniques. The instrument used in this study was MSQ. The assessment results are analyzed descriptively to determine the value of employee job satisfaction. The results of this study showed that 66.7% of employees had a level of satisfaction that was in the good category. Conclusion of this study hospital management needs to pay attention to employee satisfaction related to the achievement of work performance, employee salaries, and working environment conditions because all three elements have lower values ​​compared to other elements. So it is important for hospitals to encourage employees to improve work performance by giving employees the opportunity to develop themselves through education and training activities. As well as reviewing salaries provided and providing a conducive work environment so as to increase employee job satisfaction.